GENE-25. LOSS OF m6A RNA METHYLATION DURING GLIOMA STEM CELL DIFFERENTIATION IS REGULATED BY MIRNAS AND PROMOTES TRANSLATION EFFICIENCY. (5th November 2018) - Zepecki, John; Fajardo, Eduardo; Snyder, Kristin; Guetta-Terrier, Charlotte; Tang, Oliver; Sarkar, Atom; Fiser, Andras; Toms, Steven
Abstract: The dynamic and reversible N 6 -methyladenoside (m 6 A) affects eukaryotic mRNA localization, stability, splicing and translation. However, the role of m 6 A RNA methylation in the regulation of translation efficiency in human cancer cells is largely unknown. Here, using ribosome profiling, integrated transcriptome and m 6 A RNA sequencing analyses, we determined that as patient derived glioma cells transition from stem cells to differentiated cells, they exhibit loss of m 6 A RNA methylation and an increased rate of translation of the demethylated transcripts. We identified that the sequence motifs of the m 6 A peak regions of genes that lose m 6 A RNA during glioma stem cell differentiation, are complementary to the seed sequences of specific miRNAs. Expression of these target specific miRNAs results in loss of m 6 A RNA methylation without affecting transcript levels. Moreover, miRNAs induce cellular demethylase activity, increase the association of FTO with RNA in nuclear speckles and the binding of FTO to the miRNA-targeted and demethylated transcripts. This study highlights a critical role of m 6 A RNA methylation in regulation of translation in human cancer cells and identifies regulatory miRNAs that functionally influence the epitranscriptome during glioma stem cell differentiation.